An Electronic Algorithm to Identify Vancomycin-Associated Acute Kidney Injury - Cherian, Jerald P; Jones, George F; Bachina, Preetham; Helsel, Taylor; Virk, Zunaira; Lee, Jae Hyoung; Fiawoo, Suiyini; Salinas, Alejandra; Dzintars, Kate; O'Shaughnessy, Elizabeth; Gopinath, Ramya; Tamma, Pranita D; et al. (Open forum infectious diseases, 2023)
Abstract Background The burden of vancomycin-associated acute kidney injury (V-AKI) is unclear because it is not systematically monitored. The objective of this study was to develop and validate an electronic algorithm to identify cases of V-AKI and to determine its incidence. Methods Adults and children admitted to 1 of 5 health system hospitals from January 2018 to December 2019 who received at least 1 dose of intravenous (IV) vancomycin were included. A subset of charts was reviewed using a V-AKI assessment framework to classify cases as unlikely, possible, or probable events. Based on review, an electronic algorithm was developed and then validated using another subset of charts. Percentage agreement and kappa coefficients were calculated. Sensitivity and specificity were determined at various cutoffs, using chart review as the reference standard. For courses ≥48 hours, the incidence of possible or probable V-AKI events was assessed. Results The algorithm was developed using 494 cases and validated using 200 cases. The percentage agreement between the electronic algorithm and chart review was 92.5% and the weighted kappa was 0.95. The electronic algorithm was 89.7% sensitive and 98.2% specific in detecting possible or probable V-AKI events. For the 11 073 courses of ≥48 hours of vancomycin among 8963 patients, the incidence of possible or probable V-AKI events was 14.0%; the V-AKI incidence rate was 22.8 per 1000 days of IV vancomycin therapy. Conclusions An electronic algorithm demonstrated substantial agreement with chart review and had excellent sensitivity and specificity in detecting possible or probable V-AKI events. The electronic algorithm may be useful for informing future interventions to reduce V-AKI. An electronic algorithm using electronic health record data accurately identified vancomycin-associated acute kidney injury (V-AKI) events. Among courses of ≥48 hours of intravenous vancomycin, 14.0% resulted in an at least possible V-AKI event (22.8 cases per 1000 days of therapy).